1994
DOI: 10.1161/01.hyp.23.6.1022
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth and Na-K-Cl cotransport responses of vascular smooth muscle cells of Milan rats.

Abstract: The present study examines the role of serum growth factors in the proliferative response and Na-K-Cl cotransport activity of vascular smooth muscle cells from Milan normotensive (MNS) and hypertensive (MHS) rats. Cells from thoracic aorta of both strains were cultured in 10% serum medium and made quiescent by 72 hours in 0.3% serum medium. MHS cells grown with 10% serum had a shorter population doubling time than MNS cells between passages 8 and 12 (13.8±1.7 versus 20.1±1.6 hours, P<.01, n=4). MHS cells also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Milan hypertensive rats have also been shown to have an increased proliferative response to EGF in cultured VSMC when compared to normotensive Milan rats. In this case, however, no difference could be found in the number or affinity of the receptors for EGF [ 11 ].…”
Section: Epidermal Growth Factor and Smooth Muscle Cellsmentioning
confidence: 53%
“…Milan hypertensive rats have also been shown to have an increased proliferative response to EGF in cultured VSMC when compared to normotensive Milan rats. In this case, however, no difference could be found in the number or affinity of the receptors for EGF [ 11 ].…”
Section: Epidermal Growth Factor and Smooth Muscle Cellsmentioning
confidence: 53%
“…Most studies of the relationship between vascular smooth muscle NKCC1 and blood pressure have been limited to cells cultured from hypertensive rats. Its activity is reduced in cells cultured from aortas of spontaneously hypertensive rats (35,39) but increased in cells cultured from Milan hypertensive rats (4). Because of the phenotypic changes these cells undergo in culture (40), such results probably have little relevance to vascular smooth muscle in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the NKCC cotransporter by loop diuretics is associated with decreased proliferation of human skin fibroblasts, bovine endothelial cells, and rat vascular smooth muscle cells in culture (3,19,21). Because we have shown that a functional NKCC cotransporter is present in human airway smooth muscle (9, 10), we hypothesized that inhibition of the cotransporter with loop diuretics will also impair proliferation of different cells within the lung.…”
mentioning
confidence: 99%